1987
DOI: 10.1111/j.1365-2133.1987.tb04125.x
|View full text |Cite
|
Sign up to set email alerts
|

Infantile myofibromatosis. Report of two cases in one family

Abstract: Two brothers with infantile myofibromatosis are reported. Both had cutaneous and skeletal myofibromas with spontaneous and complete healing of their cutaneous lesions. These cases suggest autosomal recessive inheritance of this rare disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…Although most reported cases seem to be sporadic, several families with IM in more than 1 family member have also been reported. Although an autosomal‐dominant inheritance seems to be implicated in some reports, an autosomal‐recessive mode of inheritance seems to be supported by other studies [1–6].…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…Although most reported cases seem to be sporadic, several families with IM in more than 1 family member have also been reported. Although an autosomal‐dominant inheritance seems to be implicated in some reports, an autosomal‐recessive mode of inheritance seems to be supported by other studies [1–6].…”
mentioning
confidence: 84%
“…A literature review revealed 7 additional families with IM in more than 1 family member. An autosomal‐recessive mode of inheritance seemed likely in five previous reports, totaling 7 pairs of siblings, with consanguinity in 1 family [2–6]. Another study of IM in an infant and her father suggested an autosomal‐dominant pattern; however, it is unknown if the marriage was consanguineous or if the father was himself the product of a consanguineous marriage [1].…”
mentioning
confidence: 99%
“…An autosomal dominant mode of inheritance seems to be supported by other studies [1,7,11]. No genetic markers have been identi®ed so far.…”
Section: Case Historymentioning
confidence: 78%
“…Treatment with progesterone was successful in patients with diverse cases of fibromatosis (8). Because IM has occurred in several family members, a familial pattern of inheritance was suggested and supported by the recognition of IM in two brothers (9). The majority of cases are sporadic, but autosomal dominant, recessive, and polygenic modes of inheritance have been proposed (10.11).…”
Section: Discussionmentioning
confidence: 99%